M.A. USMANOV'S MEETINGS WITH DAGHESTAN AND DAGHESTANIS - Usmanova, Dilara Mirkasymovna (History, Archeology and Ethnography of the Caucasus, 2018)
This article studies an expedition of 1969, in the course of which the young teacher and researcher of Kazan State University, Mirkasym A. Usmanov (1934-2010), visited Astrakhan and Makhachkala, two sites that were very important to him. The trip to Astrakhan had the goal to identify and collect Oriental manuscripts and old print works. The short visit to Makhachkala was of a different nature, namely to obtain contacts in Daghestan and get acquainted with the region. In Makhachkala young Usmanov for the first time got in touch with regional research institutes that specialized in the study of the manuscript heritage. The notes that he kept in his research diary reflect the creative manners that Usmanov designed in the study of the written heritage, his personal "laboratory". In an attachment to this article we provide, in Russian translation, a short passage from the diary parts that describe his visit to Makhachkala; the diary has not been published before. A few years later Usmanov established relations with more Daghestani colleagues; this came about in the course of the Barthold Symposiums ( Bartol'dovskie chteniia ) that, between 1973 and 1993, were regularly held in Moscow. Among these colleagues were Amri R. Shikhsaidov, with whom Usmanov developed a thorough and collegial friendship, and fruitful collaboration in a number of fields. The present article draws some parallels in the scholarly careers of these two outstanding scholars; Usmanov and Shikhsaidov both made tremendous contributions to the development of Oriental archaeography in their respective home regions, Tatarstan and Daghestan. Attachment two to this article reproduces a letter that Shikhsaidov sent to Usmanov in 1984; this document gives us a good impression about the character of the scholarly contacts between the two colleagues.
Keywords: archeographic expeditions; oriental manuscript heritage; diary; M.A. Usmanov; A.R. Shikhsaidov; Makhachkala; Daghestan